Influence of Pressure and Water Content on Loess Collapsibility of the Xixian New Area in Shaanxi Province, China (2017)
More than 40% area of the Xixian New Area is a loess deposit region, and most of the loess landform is tableland and terrace where the thickness of loess is very large. Therefore, loess collapsibility will be the most important geotechnical problem in future foundation investigation and construction. To explore loess collapsibility in the Xixian New Area, we conducted the K0 compression test, based on the collapsibility mechanism, which has different combinations of pressure (0~1.2 MPa) and water content (4%~Sat). Based on the σ-ε curve under different water content, we calculated the generalised collapse settlement and collapsibility coefficient of every water content under every pressure by subtracting the relevant curve from the saturated curve, and analysed the cross action of pressure and water on loess compressibility. The results show that the average collapsibility level of the northern Xixian New Area is self-weight collapsible level Ⅱ, with a lower limit of 14 m. Compressibility of loess is proportional to pressure and water content. Under low water content, the collapsibility coefficient δs increased while the pressure increased, but under medium and high water content, δs will reach peak with increasing pressure and after that, δs will decrease until its value is close to constant. When under the same pressure, δs decreases when water content increases. If set the additional strain 1.5% as collapse start criterion, then the initial collapse pressure Pi will linear proportional to water content. The initial collapse water content wi will increase sharply when pressure increases under low pressure, but wi will reach a constant value of 26% when pressure is larger than 200 kPa. This consequence will be meaningful for future geotechnical investigation and design in the Xixian New Area.